Strategic architecture as a concept towards explaining the variation in performance of networked era firms - G. M. Mansfield; L. C.H. Fourie; W. R. Gevers (South African Journal of Business Management, 2005)
In a previous article the authors suggested for networked era firms that latent performance benefits could be found at the confluence of strategy and business models. They argued that the internet and its open standards created an environment making new demands on business that transcend traditional boundaries and call for new patterns of management behaviour.Using these concepts as a starting point, this article develops a construct, strategic architecture, posited as a fundamental, pervasive business phenomenon characterising successful ventures.Finding strategic intent underpinning strategy and value-creation driving business models, the additional dimensions of dynamic pliancy and harmony are developed. The article concludes with a synopsis of the other literature-based dimensions of the strategic architecture construct which are posited as futurity, customer centricity, market exploitability, economic innovativeness, interjacency, digital spontaneity and scalability, knowledge management, innovative aggressiveness and equivocality.
Keywords: 650